HUBUNGAN USIA AWAL PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN STATUS ANTROPOMETRI PADA ANAK USIA 9-12 BULAN - Diah Pratiwi Widiastuti; Riri Novayelinda; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Complementary foods (MP-ASI) are food given to infants older than 6 months to meet nutritional needs other than breastmilk. This study aimed to determine the relationship between complementary feeding (MP-ASI) with anthropometric status on children aged 9-12 months around posyandu working area of Puskesmas Harapan Raya Pekanbaru. This research was a descriptive correlation with cross sectional approach. Samples were 61 respondents taken based on inclusion criteria using proportional random sampling. The instrument used is questioner about firts age of complementary feeding and weight and height scales. This study showed that were given complimentary feeding at 6 month old 78,7% (48 infant). This research also found as many as 44.1% (43 infants) with good nutritional status. Kolmogorov-Smirnov analysis show that p value (1,000) > α (0,05) that means that there is no significant relationship between the early age of complementary feeding (MP-ASI) with anthropometric status in children aged 9-12 months.this study suggestions for parents to provide complementary feeding (MP-ASI) to their child age and always monitor the child's development and growth. Keywords : Anthropometric Status, 6-9 months infant, Complementary food (MP-ASI)